Analysis of the extracts from gaharu wood of aquilaria malaccensis lamk : by gas chromatography-mass spectrometry - Mohd. Marsin Sanagi, 1956-; Muhamad Khairul Jamaludin; Low, Yee Mean; Imma Suria Ishak; Malaysian Chemical Congress (2002 : Kuching, Sarawak) (Skudai : Universiti Teknologi Malaysia, 2002)
50